2012
DOI: 10.1590/s0066-782x2012001300012
|View full text |Cite
|
Sign up to set email alerts
|

Uso inapropriado da ecocardiografia transtorácica, segundo recomendações da SBC

Abstract: Background: Guidelines from medical societies suggest recommendations for the appropriate request of tests. In 2009, the Brazilian Society of Cardiology (BSC) published new guidelines for transthoracic echocardiography (TTE) request.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Some studies showed a marked increase in the number of echocardiogram requests in recent years (6–8% per year) ( 3 , 5 ). In Brazil (2010), 715,655 elective echocardiograms were performed in outpatients in the Unified Health System (SUS), and 425.317 (59%) of them were performed in the southeastern region of the country, with an estimated cost of over R$ 30 million ( 6 ), contributing to a progressive increase of public health costs ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies showed a marked increase in the number of echocardiogram requests in recent years (6–8% per year) ( 3 , 5 ). In Brazil (2010), 715,655 elective echocardiograms were performed in outpatients in the Unified Health System (SUS), and 425.317 (59%) of them were performed in the southeastern region of the country, with an estimated cost of over R$ 30 million ( 6 ), contributing to a progressive increase of public health costs ( 7 ).…”
Section: Introductionmentioning
confidence: 99%